Shunt capacitor bank series group shorting (CAPS) design and application. - Bruns, D.P.
This paper highlights results of a design study to optimize CAPS (capacitor bank series group shorting) as applied to EHV and HV shunt capacitor banks. The study concluded that CAPS can be built from standard, commercially available components, and can have economic advantage over conventional shunt capacitor banks in certain applications. While technically viable, the challenge is finding applications where the benefits are great enough to overcome the reluctance to try something new. Described are application considerations and possible applications evaluated at BPA
Keywords: 500 kV; EHV shunt capacitor banks; HV shunt capacitor banks; Commercially available components; Economic advantage; Reactive power; Reactive power compensation; Shunt capacitor bank series group shorting; Voltage collapse; Voltage quality